Rozwiąż równania:
a)34-7x=3x+14
b)0,5-7=23
c)3(2x+1)=5(1-x)
d)3(x-1)-2=12-(4-x)
e)4(x-2)=2(x-3)+9
f)6(y-2)+5=4(0,5-3)
Zad.2
Rozwiąż równania:
a)-4(5-6z)-9(3z-2)=2
b)05(4x+3)=2(9x-1)-3(2x=1)+4
c)-7(3x+5)-4(-2+x)=3(6x-1)+3(-x-1)
d)-[-9+2(1-2x)+(4x-3)]=5x-1

2

Odpowiedzi

2010-01-28T16:22:56+01:00
A)34-7x=3x+14
-7x-3x=14-34
-10x=-20/:(-10)
x=2
b)0,5-7=23
c)3(2x+1)=5(1-x)
6x+3=5-5x
6x+5x=5-3
11x=2/:11
x=0,181818
d)3(x-1)-2=12-(4-x)
3x-3-2=12-4+x
3x-x=8+5
2x=13/:2
x=6,5
e)4(x-2)=2(x-3)+9
4x-8=2x-5+9
4x-2x=4+8
2x=12/:2
x=6
f)6(y-2)+5=4(0,5-3)
6y-12+5=2-12
6y=10+7
6y=17/:6
y=2,833333
1 1 1
Najlepsza Odpowiedź!
2010-01-28T17:05:49+01:00
A) 34-7x=3x+14
-7x-3x=14-34
-10x=-20
x=2
b) 0,5-7=23
a gdzie x?
no to mamy dwie mozliwosci:
albo:
0,5x-7=23
0,5x=23-7
0,5x=16/÷0,5
x=32
albo:
0,5-7x=23
7x=23-0,5
7x=22,5
x=około 3
c) 3(2x+1)=5(1-x)
6x+3=5-5x
x=2
d) 3(x-1)-2=12-(4-x)
3x-3-2=12-4+x
2x=13
x=6,5
e) 4(x-2)=2(x-3)+9
4x-8=2x-6+9
2x=11
x=5,5
f) 6(y-2)+5=4(0,5-3)
6y-12+5=2-12
6y=-3
y=-1/2
2.
a) -4(5-6z)-9(3z-2)=2
-20+24z-(27z-18)=2
-20+24z-27z+18=2
-3z=4
z=-4/3
b) 0,5(4x+3)=2(9x-1)-3(2x+1)+4
rozumiem że ten "równa się" w nawiasie to miał być plus?
2x+1,5=18x-2-6x-3+4
-10x=0,5
x=-0,05
c) -7(3x+5)-4(-2+x)=3(6x-1)+3(-x-1)
-21x-35+8-4x=18x-3-3x+3
-40x=27
x=-27/40
d)-[-9+2(1-2x)+(4x-3)]=5x-1
-[-9+2-4x+4x-3]=5x-1
-[-10]=5x-1
10=5x-1
5x=11
x=11/5=2 1/5
1 3 1